PENGARUH BRAND AWARENESS DAN BRAND LOYALTY TERHADAP KEPUTUSAN PENGUNJUNG KE MONKEY FOREST UBUD - Krisnayanti, Ni Luh Made; Kusuma Negara, I Made; Dewi, NGAS. (Jurnal IPTA, 2023)
One of the factors for someone to visit a tourist attraction is because of brand awareness and brand loyalty. Both of these can increase, reach and retain consumers or visitors in deciding to visit an attraction. One of the known attractions in Bali is the Monkey Forest. This research was conducted to know the effect of brand awareness and brand loyalty on the decision of visitors to visit the tourist attraction of Monkey Forest Ubud. The operational definition of the variables used in this study uses brand awareness (X1), brand loyalty (X2) and visiting decisions (X3) variables. Data collection techniques using observation, literature study, interviews and distributing questionnaires with the help of google form. The sample in this study was determined using the Slovin formula so that 100 respondents were found. The data analysis technique of this research is descriptive quantitative with ordinal regression analysis. The results of this study indicate that the Fitting Information Model has a significance value of 0.000 0 (0.05), indicating that there is a strong correlation between Brand Awareness and Brand Loyalty simultaneously on the decision to visit the Monkey Forest Ubud tourist attraction, in a positive direction. This can be seen based on the results of the Pseudo R-Square table showing that the coefficient of determination (R square) includes the Cox and Snell value of 0.770 (77.0%), Nagelkerke's 0.817 (81.7%) and the McFaden value of 0.513 (51.3%). That is, the Nagelkertke coefficient (81.7%) which means that 81.7 brand awareness and brand loyalty variables affect the decision to visit, while 18.3% is influenced by other factors not included in the model test.